THE SIGNIFICANCE OF AGRICULTURAL COOPERATIVE SOCIETIES IN ALLEVIATING FOOD INSECURITY: A STUDY IN KWARA STATE, NIGERIA - Adegoke, Temitope Damilola; Agbasi, Obianuju Emmanuela (Journal of Allied Research in Management and Entrepreneurship (JARME), 2023)
The history of cooperative farming practices among farmers in Yoruba land dates back to periods when they would collaborate and work on each other’s farms in a rotational manner. However, food insecurity has been a prevalent issue among black communities, particularly in Nigeria, due to factors such as climate change, economic development, and violent conflicts. This study aims to evaluate the effectiveness of agricultural cooperative societies in promoting food security in Nigeria. The country has experienced worsening food insecurity over the past 15 years, as reported by the Food and Agriculture Organization. Climate change has led to increased frequency of environmental disasters, including floods, storms, and earthquakes. The unstable economy and violent conflicts, such as the Boko Haram insurgency and inter-tribal wars, further contribute to the underdevelopment and food insecurity in the country. Food security is a fundamental human requirement, and despite some reduction in the number of people experiencing hunger in previous years, it has begun to increase again since 2015. Billions of people still live with moderate to severe food insecurity, lacking regular access to food or facing its complete unavailability. Agricultural cooperative societies are voluntary organizations established to serve the common economic interests of their members and provide goods and services to enhance income, savings, productivity, and purchasing power while promoting equitable distribution of net surplus. These societies play a crucial role in supporting farmers and traders in the agricultural sector. They encourage participation in farming, offer grants, support, and assistance to members, and address various social and economic challenges faced by farmers. This study explores the objectives, mission, challenges, and impact of agricultural cooperative societies in Kwara State, Nigeria, and highlights the issues encountered by farmers in their engagement with these societies.